Albania Public Finance Review : Part 2. Improving the Efficiency and Quality of Public Spending - World Bank (Washington, DC, 2014)
Albania's rapid growth in the decade up to the 2008 global financial crisis propelled it to middle-income status and helped to reduce poverty. The global financial crisis in 2008 slammed the brakes on Albania's largely domestic-demand-driven growth. The government has accumulated sizable arrears in payments for public works and value-added tax (VAT) refunds. In a baseline scenario of no policy reforms, Albania's public debt-to-gross domestic product (GDP) ratio is projected to reach 73.5 percent in 2015 and stay above 72 percent over the medium term. Empirical evidence confirms that high public debt depresses economic activity and significantly increases the probability of default. This report examines closely the opportunities for fiscal consolidation on both the revenue and expenditure sides. Combined effect of structural reforms will reduce Albania's public debt to GDP ratio significantly over the medium term. It can in parallel rebalance its capital spending, particularly in transport, toward maintenance to support growth. Albania needs to strengthen its institutions to reinforce financial discipline and strengthen fiscal policy. Institutional reforms are particularly needed with regard to public financial management (PFM) and introducing a fiscal rule to anchor policy over the medium term.